EFFECT OF STOCKING DENSITY ON GROWTH AND SURVIVAL OF OMPOK BIMACULATUS (BLOCH) LARVAE - Debnath, Chandan; Dube, Kiran; Sahoo, Lopamudra; Datta, Mrinmoy (Journal of Indian Fisheries Association, 2014)
The study was aimed at evaluation growth and survival of Ompok bimaculatus larvae at different stocking densities (2,4,6,8 and 10 larvae/litre) during their nursery phase. Total length, weight, growth rate, percent weight pain and survival rate of larvae were found to decrease significantly with increased stocking density level of 8 larvae/ litre and above at the end of second and fourth week of rearing period. Total biomass content (g/L) increased significantly at stocking density level of 6 larvae/litre onwards. Considering the value of growth and survival rate, the stocking density level of 6 larvae/ litre was identified as optimum for nursery rearing of O.bimaculatus larvae.Â Key words: Ompok bimaculatus, growth rate, weight gain, survival rate.Â  Â